Timber management with variable retention in Nothofagus pumilio forests of Southern Patagonia - Martínez Pastur, Guillermo José; Lencinas, María Vanessa; Cellini, Juan Manuel; Peri, Pablo Luis; Soler Esteban, Rosina Matilde (Elsevier, 2025)
Forestry practices integrating ecological and social criteria have been replacing those based only on economic values. Traditional silviculture, such as shelterwood cuts (SC), transforms uneven-aged original stands to an even-aged managed forest. Recently, other methods have proposed to conserve some of the original heterogeneity of the old-growth forests. One proposal leaves 30% of the timber quality forest area as aggregated retention and 20% basal area as dispersed retention. The aim of this study was to analyze the feasibility of timber management with aggregated and dispersed retention in Nothofagus pumilio old-growth forests by analyzing timber and harvesting yield potential compared with traditional regeneration systems. Also, remnant tree stability of aggregated retention was analyzed. Timber yield potential of old-growth forests varied from 136 to 479 m3 ha1 across a site quality gradient. High grading cutting improved yield index (timber volume and harvested basal area (HBA) ratio of 7.9 m3 m2). In contrast, this index decreased in clear-cuts (4.7 m3 m2) and shelterwood cuts (4.9 m3 m2). The index also decreased in the aggregated and dispersed retention treatment (5.1 m3 m2), but with higher timber harvested volumes. Windthrow of remaining trees in aggregated retention was related to time, being significantly higher during the first year after harvesting. Windthrow was affected by crown class and position into the aggregates of the remnant trees as well as site quality of the stand. Regeneration methods with aggregated retention were feasible across the entire site quality gradient, and economic losses were not significant when compared to shelterwood cuts. The method also resulted in stability of the remnant overstory, which maintained the ecological conditions to ensure biodiversity conservation and continuity of harvested stands.